1996
DOI: 10.1152/jappl.1996.80.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Modification of circadian body temperature rhythm during the luteal menstrual phase: role of melatonin

Abstract: In women during early follicular phase (FP), the rise of melatonin at night accounts for 40% of the nocturnal core body temperature (Tc) decline. In seven normal-cycling women, the circadian rhythms of Tc and melatonin of the FP were compared with those of the luteal phase (LP). In addition, in both phases the Tc response to daytime melatonin administration was investigated. Melatonin levels were comparable during the two menstrual phases, but the nocturnal melatonin onset was delayed by 90 min in the LP (P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
80
4

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 0 publications
14
80
4
Order By: Relevance
“…The direction and magnitude of DLMO and CBT minimum phase shifts also were positively related, demonstrating a direct effect on the circadian timing system, similar to other studies (8,18,20,23,30,39,58). DLMO occurred a little over 7 h before CBT minimum, at baseline and after exposure, with a positive relationship between the two markers, as has been reported previously (7,9,14,23).…”
Section: Discussionsupporting
confidence: 88%
“…The direction and magnitude of DLMO and CBT minimum phase shifts also were positively related, demonstrating a direct effect on the circadian timing system, similar to other studies (8,18,20,23,30,39,58). DLMO occurred a little over 7 h before CBT minimum, at baseline and after exposure, with a positive relationship between the two markers, as has been reported previously (7,9,14,23).…”
Section: Discussionsupporting
confidence: 88%
“…Our data indicated that rhesus also have a periovulatory increase in mean T b , albeit earlier in the menstrual cycle than humans (i.e., 2 days before the E1C peak, which is 2-3 days before ovulation). Additionally, in contrast to the human literature [Cagnacci et al, 1996[Cagnacci et al, , 1997[Cagnacci et al, , 2002Driver et al, 1996;Lee, 1988;Severino et al, 1991] there was no difference in mean T b between the follicular and luteal phases. An increase in progesterone during the luteal phase is generally thought to be the cause of the increase in human body temperature [Cagnacci et al, 1997].…”
Section: Discussioncontrasting
confidence: 73%
“…We observed an increase in mean T b before the E1C peak, and some T b is one of the most commonly studied markers of circadian rhythmicity in humans. Some of the current human literature reports an increase in mean T b following ovulation, in the luteal phase of the menstrual cycle [Cagnacci et al, 1996[Cagnacci et al, , 1997Driver et al, 1996;Lee, 1988;Severino et al, 1991]. In fact, the increase in basal T b following ovulation is used as one of the markers for family planning [De Leizaola-Cordonnier, 1995].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time between the baseline DLMO and the start of the 1st morning bright light pulse was 8.6 ± 1.5 h in the continuous light group and 9.2 ± 1.2 h intermittent light group, but these were not significantly different, [t(17) = -0.97, p = 0.35]. Several studies have shown that the average interval between the DLMO and the Tmin is 7 h (e.g., Cagnacci et al, 1996;Brown et al, 1997;Eastman et al, 2000). Thus, we estimate that the interval between the baseline Tmin and the start of the 1st bright light pulse was 1.5 to 2 h (remember wake time on 1st day of treatment was 1 h earlier than baseline).…”
Section: Resultsmentioning
confidence: 96%